CORPORATE ORGANS’ ACCOUNTABILITY IN CASE OF SOLE PROPRIETORSHIP BANKRUPTCY - Widyaningrum, Cokorda Istri Sri Dharma; Bagiastra, I Nyoman (YURIS: Journal of Court and Justice, 2024)
Job creation provides ease of doing business for the public, especially MSMEs, by allowing them the opportunity to start their own company, which can be founded by one person or can be called as a sole proprietorship. The allowance of forming a limited liability company by one person for MSME business actors has caused legal uncertainty whether its Shareholder General Assembly, Board of Directors, and Board of Commissioners can be appointed by one person, since the Job Creation Law has not amended the provisions of Article 1 point 2 of Law No. 40/2007 on Limited Liability Companies which stipulates that the company’s organs must include the General Meeting of Shareholders, Board of Directors, and Board of Commissioners. This research used normative legal research methods combined with statutory and conceptual approaches. Based on the provisions of Article 7 Paragraphs (1) and (2) of Government Regulation No. 8/2021 concerning that a sole proprietorship company is set up with a deed of establishment equipped with identification of the founders or directors and shareholders of the sole proprietorship company, the company’s organ position in a sole proprietorship company only consists of directors and shareholders, excluding commissioners. Liability when bankruptcy occurs due to negligence or fault of the management can be held personally liable, while shareholders can only be liable to their extent due to the shares they own in the sole proprietorship.